ob satisfaction among chain community pharmacists: results from a pilot study - Hincapie AL; Yandow S; Hines S; Martineau M; Warholak T (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Objectives: The objectives of this study were to obtain pilot data concerning the job satisfaction of Tucson area retail chain setting and to identify the facets of community practice that have the greatest contribution to job satisfaction.Methods: This was a cross-sectional study of chain pharmacists in the Tucson area. The Warr-Cook-Wall questionnaire of job satisfaction was used to evaluate community pharmacists' satisfaction with their current position. This study used Rasch analysis to assess the validity and reliability of the questionnaire. The Rasch scores obtained for each respondent were used as a dependent variable in univariate and bivariate analyses to evaluate differences in job satisfaction.Results: A total of 32 pharmacists responded from 129 chain community pharmacies in the cities of Tucson, Marana and Oro Valley, Arizona. The mean (SD) Rasch score for job satisfaction was 0.93 (2.1). Results from bivariate analysis indicate that pharmacists in the Tucson area with practice experience outside community pharmacy were less satisfied with their job compared to those without experience outside community pharmacy (p<0.01).Conclusions: This pilot evaluation suggests that having pharmacy experience outside community practice affects pharmacist job satisfaction. Additionally, findings from this study indicate that there is reliability and validity evidence to support the use of the use of the Warr-Cook-Wall questionnaire for assessing overall job satisfaction in chain community pharmacy practice.